Empirical Analysis of PowerPoint Projector Use on Secondary School Performance in Physics and Chemistry in Malawi: Analisis Empiris Penggunaan Proyektor PowerPoint terhadap Performa Siswa Sekolah Menengah pada Mata Pelajaran Fisika dan Kimia di Malawi - Arnold Valaro; Sydney Kamtukule; Moses Nyasulu (SiRad: Pelita Wawasan, 2026)
This comprehensive empirical study investigates the impact of PowerPoint projector technology on academic performance in Physics and Chemistry across diverse secondary school settings in Malawi. Utilizing a quasi-experimental design with paired observations, the research analyses examination scores from 247 students across Forms 1–4 in five educational institutions. The findings reveal a statistically significant improvement in Chemistry performance with projector use (mean increase of 2.6 points, p=0.03, Cohen's d=0.22), while Physics shows minimal overall gains (mean increase of 1.6 points, p=0.12). Crucially, the study identifies a systematic pattern of teacher qualification mismatch, where Physics classes using projectors were predominantly taught by teachers with Chemistry qualifications. This misalignment potentially undermines technological benefits. The research demonstrates that lower-performing students benefit disproportionately from projector instruction, suggesting equity-enhancing potential. The study concludes that Power Point projector effectiveness is mediated by pedagogical alignment, teacher expertise, and subject-specific requirements rather than being an inherent property of the technology. Recommendations include integrated teacher training programs, strategic resource allocation aligned with teacher specialization, and development of context-appropriate digital content. [Studi empiris komprehensif ini menyelidiki dampak teknologi proyektor PowerPoint terhadap performa akademik dalam mata pelajaran Fisika dan Kimia di berbagai setting sekolah menengah di Malawi. Menggunakan desain kuasi-eksperimental dengan observasi berpasangan, penelitian ini menganalisis skor ujian dari 247 siswa di Kelas 1–4 (Form 1–4) di lima institusi pendidikan. Temuan menunjukkan peningkatan yang signifikan secara statistik pada performa Kimia dengan penggunaan proyektor (peningkatan rata-rata 2,6 poin, $p=0,03$, Cohen's $d=0,22$), sementara Fisika menunjukkan keuntungan keseluruhan yang minimal (peningkatan rata-rata 1,6 poin, $p=0,12$). Hal yang krusial, studi ini mengidentifikasi pola sistematis ketidaksesuaian kualifikasi guru, di mana kelas Fisika yang menggunakan proyektor didominasi oleh guru dengan kualifikasi Kimia. Ketidaksesuaian ini berpotensi merusak manfaat teknologi. Penelitian menunjukkan bahwa siswa dengan performa rendah mendapat manfaat yang jauh lebih besar dari pengajaran menggunakan proyektor, yang menunjukkan potensi peningkatan ekuitas. Studi ini menyimpulkan bahwa efektivitas proyektor PowerPoint dimediasi oleh keselarasan pedagogis, keahlian guru, dan persyaratan khusus mata pelajaran, alih-alih menjadi sifat bawaan dari teknologi tersebut. Rekomendasi mencakup program pelatihan guru yang terintegrasi, alokasi sumber daya strategis yang diselaraskan dengan spesialisasi guru, dan pengembangan konten digital yang sesuai dengan konteks.]